Hubungan Antara Umur dan Kebiasaan Merokok dengan Keluhan Musculoskeletal Disorders pada Operator Gantry Luffing Crane - Winny Rosemillen; Endang Dwiyanti (Universitas Airlangga, 2023)
Background: Musculoskeletal disorders (MSDs) is a series of pain felt in muscles, tendons, and nerves that arise from continuous exposure to static loads over a long period of time. MSDs complaints can be felt by various types of work including gantry luffing crane operators who work in a statically sitting and bent posture. Objectives: The aim of this study was to determine the strength of the correlation between age and smoking habit with MSDs complaints. Methods: The research was an analytic study design with cross-sectional study design. The sample selection was done by total population technique, namely 39 GLC operators at Port Services Company Jakarta in 2022. The research instrument used was Nordic Body Map for MSDs complaints. The data were analyzed using the Spearman rank test. Results: The results showed that the majority of respondents aged â‰¥ 35 years (56.4%), had a smoking habit (61.5%), and experienced high level of MSDs complaints (59.0%). Statistical tests showed the relationship between age and MSDs complaints got a correlation coefficient value of 0.528 and the relationship between smoking habits and MSDs complaints got a correlation coefficient value of 0.028. Conclusions: There is a strong relationship between age and complaints of MSDs and a very weak relationship between smoking habits and complaints of MSDs. Both age and smoking habits have a positive correlation direction with MSDs complaints. Keywords: Operator GLC, Musculoskeletal Disorders, Age, Smoking Habit